Peran Civil Society dalam Perumusan RPJPD Provinsi Sumatera Barat 2025-2045 - Marwansyah, Marwansyah; Zetra, Aidinil; Ekha Putera, Roni (Policy, Law and Political Research Center, 2025)
The drafting of the 2025–2045 West Sumatra Provincial Long-Term Development Plan (RPJPD) requires the substantive involvement of civil society organizations (CSOs) to ensure democratic, high-quality, and sustainable development planning. The role of CSOs is important given the strong socio-cultural character of West Sumatra, particularly the value of “bulek aia dek mufakat” which emphasizes deliberation in decision-making. This study aims to analyze the role of CSOs in the agenda for drafting the 2025–2045 West Sumatra Provincial RPJPD. The method used is qualitative research with an intrinsic case study approach. Informants were selected using purposive sampling, while data analysis was conducted based on the informants' perspective (emic) validated through data triangulation. The researcher used policy advocacy theory in this study. The results show that the role of CSOs in the formulation of the RPJPD can be divided into three categories: zero participation, token participation, and delegated participation. The findings show that most CSOs still have a low level of participation, while substantive participation is only carried out by a handful of CSOs. Of the forty-three (43) organizations invited, only about five (5) CSOs are officially registered with the West Sumatra Provincial Kesbangpol Agency. In general, the role of CSOs in regional development planning is not yet optimal and is still normative-administrative in nature, Meanwhile, CSOs are required to increase their advocacy capacity in order to defend the public interest and ensure that their ideas are integrated into planning documents, particularly the 2025–2045 West Sumatra RPJPD.